Richard Wingfield Stuart sketchbooks - Stuart, R. W. (Richard Wingfield), 1843-1914 (1862)
Richard Stuart's sketchbooks comprise observational sketches of Stuart's life and travels, and the society in which he moved. Stuart came to Australia at the age of 19 and worked on farming properties, sketching what he saw. Success in Australia enabled Stuart to travel back and forth between Australia and England. The subjects of the sketches include farmyard animals and farming activities, mustering cattle, travels in the country, looking for water, accidents with buggies, and horses and horsemanship. The sketches are often humorous, and reveal something of social life and expectations.
Title devised by cataloguer based on information from acquisition documentation.
Albums are leatherbound with gilt titles.
Also available online
Donated through the Australian Government's Cultural Gifts program by Mary Rose Wingfield Collom, 2006.
Keywords: Stuart, R. W. -- 1843-1914 -- Notebooks, sketchbooks, etc; Landscape drawing, Australian -- 19th century -- Pictorial works; Landscape drawing -- England -- 19th century -- Pictorial works; Landscape drawing -- United States -- 19th century -- Pictorial works; Landscape drawing -- Ireland -- 19th century -- Pictorial works; Animals -- Australia -- Pictorial works; Horses -- Australia -- Pictorial works; Australian poetry -- 19th century